Nature Inspired and Transform Based Image Encryption Techniques: A Comparative Study - Bhagyashri Pandurangi R; Chaitra Bhat; Meenakshi R. Patil (Advances in Science, Technology and Engineering Systems Journal, 2020)
In this paper, performances of two variations of chaos based algorithms are compared. First algorithm is a self-adaptive color image encryption algorithm is proposed based on Radial Hilbert Transform and chaos. This technique uses chaotic random phase masks operated on the transformed pixels to increase the randomness in confusion and diffusion operations. Also, a random jumbling process is used at the final stage to increase the randomness in the cipher image. Part of the plain image is used to generate the keys for encrypting another part. Second algorithm is inspired by the bio operations resembling confusion and diffusion. Use of a scrambler improves the performance of this algorithm. Proposed work elaborates the results of the suitability analysis conducted on various kinds of input images, namely, satellite images, face images and handwritten signature images. Performance parameters considered for the analysis include horizontal correlation, vertical correlation, diagonal correlation, and net changing pixel rate, unified average change in intensity, entropy and encryption time taken by the encryption techniques.
Keywords: Bio inspired techniques; Chaotic maps; Fractional transforms; Radial Hilbert transforms; Transform domain encryption